Asupan dan Status Gizi Remaja Putri di Kabupaten Sukoharjo - Talitha Miftah Raharjati; Listyani Hidayati; Muwakhidah Muwakhidah (FORIKES, 2023)
Malnutrition and excess nutrition can occur in children and adults, as well as in young women. This study aimed to determine the relationship between energy, protein, fat and carbohydrate intake and the nutritional status of adolescent girls. This research implemented a cross-sectional design, involving 200 young women in Sukoharjo Regency who were selected using a multistage sampling technique. Energy, protein, fat and carbohydrate intake data were measured using the Semi Quantitative Food Frequency Questioner (SQ-FFQ) method. Nutritional status was measured based on anthropometry, namely height and weight, then categorized based on body mass index indicators according to age. Hypothesis testing was carried out using Kendall's tau test. The results of the analysis showed that the intake in the good category for energy was 30%, protein intake was 34%, fat was 8%, and carbohydrates was 53.4%. The results of the correlation test show that the p value for each factor was energy = 0.056, protein = 0.086, fat = 0.060, and carbohydrates = 0.106. Furthermore, it was concluded that there was no significant relationship between energy intake and macronutrients consumed by adolescent girls and nutritional status.Keywords: energy intake; macronutrients; nutritional status; teenage girl ABSTRAK Kekurangan dan kelebihan gizi dapat terjadi pada anak-anak hingga orang dewasa, demikian pula pada remaja putri. Penelitian ini bertujuan untuk mengetahui hubungan antara asupan energi, protein, lemak, dan karbohidrat dengan status gizi remaja putri. Penelitian ini menerapkan rancangan cross-sectional, yang melibatkan 200 remaja putri di Kabupaten Sukoharjo yang dipilih dengan teknik multistage sampling. Data asupan energi, protein, lemak, dan karbohidrat diukur dengan metode Semi Quantitative Food Frequency Questioner (SQ-FFQ). Status gizi diukur berdasarkan antropometri yaitu tinggi badan dan berat badan, kemudian dikategorikan berdasarkan indikator indeks massa tubuh menurut umur. Uji hipotesis dilakukan menggunakan uji Kendall’s tau. Hasil analisis menunjukkan bahwa asupan dengan kategori baik pada energi sebesar 30%, asupan protein 34%, lemak 8%, dan karbohidrat 53,4%. Hasil uji korelasi menunjukkan nilai p untuk masing-masing faktor adalah energi = 0,056, protein = 0,086, lemak = 0,060, dan karbohidrat = 0,106. Selanjutnya disimpulkan bahwa tidak terdapat hubungan yang signifikan antara asupan energi dan zat gizi makro yang dikonsumsi remaja putri dengan status gizi.Kata kunci: asupan energi; zat gizi makro; status gizi; remaja putri